PENERAPAN MODEL BLENDED LEARNING DENGAN PERBANTUAN GOOGLE CLASSROOM UNTUK MENINGKATKAN KEMAMPUAN MEMBACA TEKS PROCEDURE - Dayadi, Agung (Jurnal Analisis Pendidikan Sosial, 2024)
This action research is based on the background of low response and low score on English learning outcome in home learning situation. This research is aimed to know and to explain the students’ reading ability of procedure text through blended learning assested google classroom. The participants were 36 students selected by purposes technique. This reseach instruments were test and non test. The test instrument consisted about procedure text, in multiple choise test. The non test was observation paper. The procedure of collecting data used google classroom dan observation was done by using observation paper/ check list. Analizing data was done by simple statistic, that is the percentage from accumulation of students’ achievement score and followed by observing result interprestation from the students’ activities. The result of this reseach on 1 st cycle showed that the percentage students’ who achieved minimal criteria was 25%, The 2nd cycle achieved 94,4%. Based on the result it can be concluded that teaching and learning using blended learning assested google classroom can increase the students’ reading ability on the middle level. Thus, Basen the achieved result, it can be suggested to teachers, students, reaseacher to read this result of the research and to analyzing deeply through futher reseach.